The making of the Irish Protestant ascendancy the life of William Conolly, 1662 - 1729 - Walsh, Patrick Paul 1966- (Irish historical monographs series, 2010)
Thit title looks at the life and political career of William Conolly, a key figure in the establishment of the 18th-century Protestant ascendancy in Ireland